PENINGKATAN KUALITAS SUPERVISI PENDIDIKAN DALAM PENINGKATAN MUTU LEMBAGA PENDIDIKAN ISLAM DI MA MIFTAHUL ULUM AN-NUR BANTARAN PROBOLINGGO - Badriyatul Hilmi Al Ummah; Zakariyah Zakariyah; Muhammad Nawawi (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This study aims to examine efforts to improve the quality of Islamic educational institutions at MA Miftahul Ulum An-Nur through educational supervision. Using a qualitative method with a case study approach, this study explores the institution's quality conditions, improvement efforts, and supporting and inhibiting factors. Data were obtained through interviews, observations, and document analysis with participants including the principal, teachers, students, and foundation members. The results indicate that quality improvement is carried out through the development of an Islamic values-based curriculum, teacher training, and extracurricular programs. Supporting factors include foundation support, commitment of educators, and cooperation with parents. Inhibiting factors include inadequate teacher qualifications, limited facilities, and a lack of understanding among parents. Educational supervision has not been optimal in supporting effective learning. These findings provide insights for Islamic educational institutions in managing and continuously improving quality.